Managing big data in cloud computing environments - Ma, Zongmin (Advances in systems analysis, software engineering, and hight performance computing (ASASEHPC) book series., 2016)
This book explores the latest advancements in the area of data management and analysis in the cloud, providing timely, research-based information relating to data storage, sharing, extraction, and indexing in cloud systems.